2011
DOI: 10.1063/1.3573759
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Cullet-Clay Ceramic

Abstract: Articles you may be interested inGrowth and texture of spark plasma sintered Al2O3 ceramics: A combined analysis of X-rays and electron back scatter diffraction Effects of mesh-assisted carbon plasma immersion ion implantation on the surface properties of insulating silicon carbide ceramics Abstract. A series of ceramic based on (x) cullet-(100-x) clay has successfully been made by slip casting followed by sintering at 800 o C. The sample density has been determined using the Archimedes method while their hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…From Table 1, it can be seen that as the titanium nitride content is increased while the cullet content is decreased, the color of sample obtained is changing from whitish to yellowish. The changing in color of the sample might indicate that there are lots of transition elements in the mixture [12]. Furthermore, Table 1 also Figure 1 shows a typical result of X-ray diffraction for some samples at different cullet-TiN level after being sintered at 1000 ºC.…”
Section: Resultsmentioning
confidence: 99%
“…From Table 1, it can be seen that as the titanium nitride content is increased while the cullet content is decreased, the color of sample obtained is changing from whitish to yellowish. The changing in color of the sample might indicate that there are lots of transition elements in the mixture [12]. Furthermore, Table 1 also Figure 1 shows a typical result of X-ray diffraction for some samples at different cullet-TiN level after being sintered at 1000 ºC.…”
Section: Resultsmentioning
confidence: 99%
“…However, not many attempts to compose new ceramics based on the mixture of glass waste and clay have been reported. In our earlier studies [8][9], it has been shown that these new ceramics can be formed with higher density, higher hardness, lower drying shrinkage, less water absorption, and other good physical qualities [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%